Selenium and Muscular Dystrophy - J Gordon Millichap (Pediatric Neurology Briefs, 1989)
Selenium metabolism and supplementation in patients with Duchenne muscular dystrophy was studied at the Muscle Research Center, Department of Medicine, University of Liverpool, and the Universitat Klinik Mainz, Mainz, FRG.